2020
DOI: 10.1371/journal.pone.0239715
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of social support group intervention for people with aphasia: A Novel application of virtual reality

Abstract: About a third of strokes cause aphasia, or language loss, with profound consequences for the person's social participation and quality of life. These problems may be mitigated by group social support. But this intervention is not available to all individuals. This study investigated whether it is feasible to deliver group social support to people with aphasia via a multiuser , virtual reality platform. It also explored the indicative effects of intervention and the costs. Intervention aimed to promote wellbein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 68 publications
2
20
0
7
Order By: Relevance
“…Very recently, Marshall et al [ 120 ] published a randomized controlled design in which a group therapy was virtually implemented in EVA Park, with patients, volunteers, and coordinators present in the VR environments. Two intervention groups were randomized to an immediate therapy condition and two were randomized to a delayed condition.…”
Section: Virtual Reality Approachmentioning
confidence: 99%
“…Very recently, Marshall et al [ 120 ] published a randomized controlled design in which a group therapy was virtually implemented in EVA Park, with patients, volunteers, and coordinators present in the VR environments. Two intervention groups were randomized to an immediate therapy condition and two were randomized to a delayed condition.…”
Section: Virtual Reality Approachmentioning
confidence: 99%
“…Most of the Clinical Trial groups listed used the methodology generally involving two groups, corresponding to 95.72% of the articles presented, a Control Group (CG) in which they apply traditional treatment procedures and the Intervention Group using Virtual Reality (GRV) with application of Virtual Reality during the treatment sessions. Some studies showed more than two groups such as Marshall [154] that used 6 groups (0.85%), Radder et al [155], Ramos et al [149], Kakoschke et al [132], Tuba et al [122], Bortone, I [118], Gerard Fluet [115], Perin, Alessandro, et al [105], Amin, Ashfaq M., et al [104], Manuli et al [88], Gerard Fluet [115] conducted their research with 3 groups (7.69%), Erdogan et al [133], Liu, Wang, et al [109], Dehghan, Fateme, et al [106] worked with 4 groups (2.56%) and 2 articles such as Ortiz-Catalan et al [94], Amaral et al [56] that used only 1 group (1.70%). Regarding the work by Kim et al [140] 2 intervention groups divided by age group.…”
Section: Group Profilementioning
confidence: 99%
“…Very recently, Marshall et al [119] published a randomized controlled design in which a group therapy was virtually implemented in EVA Park, with patients, volunteers, and coordinators present in the VR environments. Two intervention groups were randomized to an immediate therapy condition and two were randomized to a delayed condition.…”
Section: Virtual Reality Approachmentioning
confidence: 99%